Studies in Settler Colonialism
X, 307 p.
Keywords: A widespread and still contemporary political phenomenon that exercises a profound effect on societies, settler colonialism structures relationships both historically and culturally diverse. This book assesses the distinctive feature of settler colonialism, and discusses its political, sociological, economic and cultural consequences.